Efeito do cloprostenol sódico sobre a evolução uterina no puerpério de vacas nelore - Moraes, Carolina Nogueira de [UNESP] (2014)
After calving, some physiological events occur in the uterus of cows to repair the modifications occurred during pregnancy and delivery. The use of cloprostenol sodium at postpartum period aims to reduce the period of uterine involution by acting at uterine contraction, helping in reducing uterine size, at uterine cleaning, and at the resumption of ovary activity. For this, the aim of this work was to evaluate the effect of the application of cloprostenol sodium on postpartum on uterine involution, hormonal dosage of progesterone (P4) and 13,14-dihydro-15-keto prostaglandin F2 (PGMF), histological variables, mRNA expression of PGF2 receptor (FP), caspase- 3 (CASP-3) and cyclooxygenase 2 (COX-2), and also protein expression of FP and COX-2. For this, multiparous Nelore cows (n=24) were treated or not with cloprostenol sodium on days 1 and 4 postpartum (D0 = birth) and it was done ultrasound, transretal palpation, vaginoscopy exams and blood collection on D1, D7, D14, D21, D28, D35 and 42 postpartum (D0 = birth). Also, endometrial biopsies were collected with a Yomann biopsy instrument at D1, D7, D14, D28 and D42 for histological analysis, mRNA expression by qRT-PCR and immunolocalization by imunohistochemistry. According to the results, cloprostenol sodium had influence (P< 0,05) on cervical discharge and integrity and mRNA expression of CASP-3. For the variables related to hormonal dosage, uterine involution, histological variables (endometrial glands and degree of inflammation) there was observed effect only on moment and for the others, any kind of influence was noted. Based on the results, it can be conclude that the use of this protocol in multiparous Nelore cows with good genetic selection, adequate management and health can be unnecessary to reduce postpartum period and can promote additional spending. However, further studies should be conducted using cloprostenol or other analogs of PGF2 at different doses and moments of ...